Life of Pi a novel - Martel, Yann 1963- (Harcourt, 2001)
Possessing encyclopedia-like intelligence, unusual zookeeper's son Pi Patel sets sail for America, but when the ship sinks, he escapes on a life boat and is lost at sea with a dwindling number of animals until only he and a hungry Bengal tiger remain.
Keywords: Relations homme-animal - Romans, nouvelles, etc; Survie après accidents d'avion, naufrages, etc - Romans, nouvelles, etc. pour la jeunesse; Human-animal relationships -- Fiction; Ocean travel -- Fiction; Orphans -- Fiction; Psychological fiction.; Storytelling -- Fiction; Survival after airplane accidents, shipwrecks, etc. -- Fiction; Teenage boys -- Fiction; Tiger -- Fiction; Zoo animals -- Fiction; Überleben; Schiffbruch; Religion; Tiger; Indischer Jugendlicher; Faszination; Männliche Jugend; Zähmung; Pacific Ocean -- Fiction; Indien; Fiktionale Darstellung; Psychological fiction; Adventure fiction